Local Leader Tenure and Socio-Political Resilience: A Preliminary Study - Aryo Wicaksono; Moeljadi; Mohamad Anas (Publisia: Jurnal Ilmu Administrasi Publik, 2025)
Changes in policy related to the term of office of village heads, such as term extensions, have the potential to cause various negative impacts. On the one hand, this policy can be a step toward strengthening the stability of village administration. The term of office of local leaders and socio-political resilience seeks to explore research trends regarding local leadership and socio-political resilience. This analysis provides a comprehensive overview of the intellectual structure, key contributors, influential publications, and collaborative networks that shape this field. The study adopts bibliometric analysis to conduct a comprehensive and systematic search of the formal characteristics of the scientific domain, using quantitative and qualitative data from previous publications. This study found that the keywords “study” and “governance” play an important role in the tenure of local leaders and socio-political resilience. In-depth governance studies play an important role in the tenure of local leaders and socio-political resilience. This is because governance studies emphasize the importance of social and political studies of governance. Current trends show that the tenure of local leaders and social-political resilience are most frequently written about in social research topics (44%), followed by art and humanities topics (24%), and environmental topics in third place (7%).